2010
DOI: 10.1007/s10915-010-9427-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Treatment of the Loss of Hyperbolicity of the Two-Layer Shallow-Water System

Abstract: In this work, a characterization of the hyperbolicity region for the two layer shallow-water system is proposed and checked. Next, some path-conservative finite volume schemes (see [11]) that can be used even if the system is not hyperbolic are presented, but they are not in general L 2 linearly stable in that case. Then, we introduce a simple but efficient strategy to enforce the hyperbolicity of the two-layer shallow-water system consisting in adding to the system an extra amount of friction at every cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 23 publications
3
66
0
Order By: Relevance
“…So this condition is linked to the KH instability of the stratified flows [28,27]. See [14] for the numerical treatment of the loss of hyperbolicity of the two layer shallow water system, and see [10] for the nonlinear stability analysis of twolayer shallow water equations with a rigid-lid. This approach for the approximation of the eigenvalues is useful only for two-layer shallow fluid flows with densities very close to each other (Boussinesq approximation).…”
Section: Computing the Eigenvalues Of The Jacobianmentioning
confidence: 99%
“…So this condition is linked to the KH instability of the stratified flows [28,27]. See [14] for the numerical treatment of the loss of hyperbolicity of the two layer shallow water system, and see [10] for the nonlinear stability analysis of twolayer shallow water equations with a rigid-lid. This approach for the approximation of the eigenvalues is useful only for two-layer shallow fluid flows with densities very close to each other (Boussinesq approximation).…”
Section: Computing the Eigenvalues Of The Jacobianmentioning
confidence: 99%
“…The practical problem is that too much friction can results in excessively diffused results and even produce spurious oscillations in the flow. In Castro et al (2011) a different strategy for maintaining the hyperbolic character was presented. This numerical workaround is based on the predictor/corrector algorithm, which consists in adding an extra friction term only to those individual cells in which complex eigenvalues are detected at a given time step (Castro et al, 2011).…”
Section: Numerical Schemementioning
confidence: 99%
“…In Castro et al (2011) a different strategy for maintaining the hyperbolic character was presented. This numerical workaround is based on the predictor/corrector algorithm, which consists in adding an extra friction term only to those individual cells in which complex eigenvalues are detected at a given time step (Castro et al, 2011). The additional friction should simulate the loss of momentum due to mixing, which is expected in real flows as a result of interfacial instabilities.…”
Section: Numerical Schemementioning
confidence: 99%
“…In [5] it is shown that (2.5) is a good approximative criterion for the loss of hyperbolicity when r 12 is close to 1. The ratio κ can be interpreted as the 2/3-layer Shallow Water balance between the stabilizing influence of the difference in density and the destabilizing one of the velocity shear.…”
Section: Multilayer Flowsmentioning
confidence: 99%
“…Several authors have suggested such models, e.g. LeVeque and Kim [6], Castro and Pares [5], Bouchut and Morales [2] and Audusse [1].…”
Section: Introductionmentioning
confidence: 99%